PENGARUH CITRA MEREK, KUALITAS PRODUK DAN PERSEPSI HARGA TERHADAP NIAT BELI ULANG - Dewi, Putu Ratya Sandria; Seminari, Ni Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
Various brands of instant coffee that exist cause a variety of choices in the minds of consumers that can affect the repurchase intention of coffee brands. Banyuatis Coffee is one of the companies that produce instant ground coffee which is having problems with repurchasing intentions from consumers. This study aims to analyze the effect of brand image, product quality, price perception on repurchase intention. This research was conducted on consumers who have consumed and purchased Banyuatis Coffee products in Denpasar City. The number of samples determined was 105 respondents. The analysis technique uses Multiple Linier Regression Analysis, Classical Assumption Test, T Test, F Test, Determination Coefficient Test. The results showed that brand image had a significant positive effect on repurchase intentions, product quality had a significant positive effect on repurchase intentions and price perceptions had a significant positive effect on repurchase intentions of Banyuatis Coffee consumers in Denpasar City. To maintain consumer repurchase intentions by giving a positive impression of the brand in the minds of consumers, maintaining product quality, and choosing appropriate prices to create positive perceptions of prices in consumers' minds